1996
DOI: 10.1080/13537909608580778
|View full text |Cite
|
Sign up to set email alerts
|

Iconographic representations of Sri Ramakrishna and Swami Vivekananda

Abstract: Through the use of popular statuary, devotional pictures and calendars available in the markets and temple stalls of Calcutta, I compare the ways in which the legacy of Ramakrishna and Vivekananda has been preserved in popular symbolism with the 'photo-iconographic' tradition which has been fostered within the Ramakrishna Math and Mission. I argue that links between Ramakrishna and the Kali tradition remain strong in the popular imagination, as expressed through popular art in Calcutta, and that Swami Vivekana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Five photographs were taken of Sri Ramakrishna. One of them, taken in 1884, has been the object of most devotional activity and is known as the “worshipped pose” of Sri Ramakrishna—the one worshipped during the aarati service (Beckerlegge , 321; Vidyatmananda , 271) . In this image, Sri Ramakrishna sits cross‐legged in a state of samadhi , an ecstatic state of deep meditation in which the individual consciousness merges with its source–divine consciousness.…”
Section: Photography and Sri Ramakrishnamentioning
confidence: 99%
See 2 more Smart Citations
“…Five photographs were taken of Sri Ramakrishna. One of them, taken in 1884, has been the object of most devotional activity and is known as the “worshipped pose” of Sri Ramakrishna—the one worshipped during the aarati service (Beckerlegge , 321; Vidyatmananda , 271) . In this image, Sri Ramakrishna sits cross‐legged in a state of samadhi , an ecstatic state of deep meditation in which the individual consciousness merges with its source–divine consciousness.…”
Section: Photography and Sri Ramakrishnamentioning
confidence: 99%
“…Certainly most of the activities during the aarati service before Sri Ramakrishna's photograph—the garlanding, offerings of incense and food, the fanning—would be seen in a service of devotion to a murti, an object embodying the divine in the form of a statue or an image. Indeed H. Daniel Smith has suggested that photographs of holy figures be included in studies of the human iconography of desika statues who are objects of devotion (Beckerlegge , 326; Smith , 41).…”
Section: Photography and Sri Ramakrishnamentioning
confidence: 99%
See 1 more Smart Citation
“…The development of photography has been an important factor in the dissemination of transnational guru movements, both globally and into personal domestic spaces. Gwilym Beckerlegge (1996) argues that an analysis of 'photo-iconographic' images of Ramakrishna, Sarada Devi and Swami Vivekananda can shed light on how these individuals are perceived not only within the Ramakrishna Mission, but also how they are conceived in relationship to the wider Hindu community. These photographic representations of gurus reinforce the idea of their omnipresence and the idea that devotees can always have darśan of the guru, irrespective of time and space.…”
Section: God Posters Comics and Photo-iconsmentioning
confidence: 99%